Analysis of 1-Hz GPS data for the estimation of long-period surface motion of Tohoku-Oki Mw9.0 2011 earthquake - Psimoulis, Panos; Houlié, Nicolas; Clotaire, Michel; Meindl, Michel; Rothacher, Markus (2016)
The GPS displacement time series are today mostly used for the estimation of the transient (period <2sec) and coseismic (static) displacement of an earthquake, while the estimation of the velocity and acceleration is based only seismic networks. In this study, we examine whether the GPS records can be used to capture the spectral characteristics of the long-period signal and their consistency with the corresponding seismic motion sensors, for the displacement, velocity and acceleration. For this purpose, we use the 1-Hz GPS network records of the Tohoku-Oki 2011 earthquake processed in Precise Point Positioning (PPP). The derived GPS and strong-motion waveforms were analysed resulting into displacement, velocity and acceleration for periods ranging from 3 to 100s. The derived GPS and strong-motion time series were compared and it was found that these are of similar pattern and amplitude. However, there is a non-constant phase shift between the corresponding GPS and strong-motion time series, resulting in significant difference between the time series in the time domain. On the contrary in the frequency domain, the GPS and strong-motion time series are consistent for periods larger than 3-4s. Finally the GPS and the strong-motion records were compared in the time-frequency domain based on wavelet analysis, revealing that both GPS and seismic records express consistently the variation of the long-period of the seismic signal. Thus, it is proved that the GPS records can be used for the estimation of the long-period ground motion and contribute to the reliable estimation of the corresponding characteristics (displacement, velocity, acceleration).